PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI BARISAN DAN DERET DENGAN METODE REWARD - Nabila Nurul Jannah; M. Afrilianto (IKIP Siliwangi, 2022)
This research is included in classroom action research or classroom action research to examine efforts to increase students' motivation and learning outcomes after being rewarded. The hypothesis is that the method of giving rewards can be one of the efforts to increase motivation, which impacts student learning outcomes in series and sequence material in distance or online learning in class XI SMK students. The research instrument for class XI RPL-A SMK Pusdikhubad Cimahi in the 2020/2021 period was 34 people. Researchers used an instrument with an ability test to measure student learning outcomes and a questionnaire to measure their learning motivation. The data analysis technique used is the initial data analysis or requirements test which consists of normality test, homogeneity test. Then the final data analysis was carried out in the form of normality, homogeneity, T-Testm, N-Gain, and Treatment tests. Researchers found an increase in learning motivation and learning outcomes for class XI SMK students in online or online learning in the subject